Essentials of Computational Electromagnetics - Sheng, Xin-Qing, 1968-; Song, Wei. (Hoboken : John Wiley & Sons, 2012)
Essentials of Computational Electromagnetics provides an in-depth introduction of the three main full-wave numerical methods in computational electromagnetics (CEM); namely, the method of moment (MoM), the finite element method (FEM), and the finite-difference time-domain (FDTD) method. Numerous monographs can be found addressing one of the above three methods. However, few give a broad general overview of essentials embodied in these methods, or were published too early to include recent advances. Furthermore, many existing monographs only present the final numerical results.
3.4 Node-Edge Element.
Includes bibliographical references and index.
Print version record.
Keywords: Electromagnetism -- Data processing; Electromagnetism -- Mathematical models; SCIENCE -- Electromagnetism; Science; Physics; SCIENCE -- Physics -- Electricity; SCIENCE -- Physics -- Electromagnetism; Electromagnetism -- Data processing; Electromagnetism -- Mathematical models; Electronic books; Electronic books